PENGARUH SELF-EFFICACY TERHADAP KETERLIBATAN KERJA DAN KEPUASAN KERJA KARYAWAN PADA IBIS STYLES BALI BENOA HOTEL - Sari, Ni Luh Sri Wiwika; Suwandana, I Gusti Made (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the influence of Self-efficacy for work engagement and job satisfaction of employees at Ibis Styles Bali Benoa Hotel. This research was conducted at the Ibis Styles Bali Benoa Hotel is located Jl Pratama 57A Tanjung Benoa focusing on MICE field, samples were taken as many as 90 people with census method. Data collected by questionnaires by using a 5-point Likert scale to measure 15 indicators. The analysis technique used is path analysis. Research shows that self-efficacy and significant positive effect on job involvement. Second, self-efficacy and significant positive effect on job satisfaction. Third, work engagement and significant positive effect on job satisfaction. The implications of this study is that the hotel could improve oversight and maintain the level of self-efficacy and engagement work to improve employee job satisfaction.
Keywords: Self-Efficacy; Work Engagement; Job Satisfaction